Adapting virus filtration to enable intensified and continuous monoclonal antibody processing. (11th December 2020) - Bohonak, David M.; Mehta, Ushma; Weiss, Eric R.; Voyta, Greg
Abstract: Ongoing efforts in the biopharmaceutical industry to enhance productivity and reduce manufacturing costs include development of intensified, linked, and/or continuous processes. One approach to improve productivity and process economics of the polishing step (i.e., anion exchange chromatography) is to preconcentrate the product intermediate using a single‐pass tangential flow filtration step before loading on the resin. This intensification of the polishing step consequently leads to changes in product intermediate concentration for subsequent virus filtration operations, potentially impacting filter performance and methods for evaluating viral clearance. The filtrate flux performance of a virus filtration operation was evaluated with monoclonal antibody (mAb) solutions of varying concentrations. These data were used to evaluate the effect on filter sizing for a hypothetical mAb perfusion process. The optimum mAb concentration to minimize the area of the virus filter was a function of the filtration step duration and reflected the competing effects of increasing concentration and decreasing volumetric flux on the membrane productivity. mAb solutions at high and low concentrations were used to evaluate viral clearance with extended filtration times (e.g., 24–72 h) simulating continuous processing conditions. Modifications to more traditional filtration viral clearance study methods were required to avoid experimental artifacts associated with the extended filtration time. No virus passage through the filter was observed under these conditions, similar to previous results for batch processes. These data demonstrate the feasibility of obtaining effective virus removal even when mAb concentration and filtrations times are increased by up to an order of magnitude from current common practices.